ω-Euclidean domain and Laurent series - Romaniv, O.M.; Sagan, A.V. (Carpathian Mathematical Publications, 2016)
It is proved that a commutative domain R is ω-Euclidean if and only if the ring of formal Laurent series over R is ω-Euclidean domain. It is also proved that every singular matrice over ring of formal Laurent series R_X are products of idempotent matrices if R is ω-Euclidean domain.